Pengembangan Kompetensi Calon Guru SD: Desain Modul Praktikum IPA Berbasis STEM Terintegrasi Alat Peraga PjBL - Risky Richlos Sarapung (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
Motivated by the need for learning tools that can enhance science process skills and conceptual understanding of prospective elementary school teachers. Science practicum activities that have been carried out so far are still limited to conventional modules and have not been fully integrated with teaching aids produced through Project-Based Learning (PjBL). This study aims to develop a STEM-based science practicum module through PjBL-produced teaching aids that are valid, practical, and effective for prospective elementary school teachers. The research employed a research and development (R&D) approach with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were fourth-semester students of the Elementary School Teacher Education (PGSD) program at a university in North Maluku, with a total of 80 participants. Research instruments included expert validation sheets, practicality questionnaires, science process skills observation sheets, and learning outcome tests (pretest–posttest). Data were analyzed using descriptive quantitative, qualitative, and inferential methods with gain scores and paired t-tests. The results showed that the STEM-based science practicum module received a very good category from expert validators (average score 4.55), was rated practical by students (average score 4.35), and was effective in improving science process skills and learning outcomes with gain scores ranging from 0.51 to 0.62, categorized as moderate to high. It can be concluded that the developed practicum module is feasible to be used as a science learning tool in PGSD/FKIP and can help equip prospective teachers with scientific and pedagogical competencies relevant to the demands of the 21st century.